Taking stock of South African income inequality - Murray V. Leibbrandt; Vimal Ranchhod; Pippa Green (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We synthesize the findings from several recent papers on South Africa's very high income inequality. These papers use new datasets-including income tax data-and new empirical methods to investigate the drivers of household income and individual earnings inequality in South Africa. Increased returns to experience and an increased rate of return to tertiary qualifications are key drivers of a widening earnings distribution. Tax data merged with survey data show that those at the top of the earnings and income distributions have done well in both absolute and relative terms, thus increasing inequality. Direct taxes and social grants are progressive, indirect taxes are less progressive, and tax exemptions for health insurance and pension fund contributions are regressive. A significant proportion of the current middle class are vulnerable to falling into poverty. Overall, South Africa has not made progress in reducing its extreme inequality over the last decade.
Keywords: D31; H24; 330; earnings personal income tax; income distribution; South Africa; wage inequality